With whom shall I share my knowledge? A recipient perspective of knowledge sharing. Issue 2 (7th April 2015) - Zhang, Xiao; Jiang, Jane Yan
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this study is to examine knowledge-sharing phenomena from the perspective of recipients' characteristics. Specifically, this study examines the influence of knowledge recipients' competence, learning attitude and personal relationship with knowledge sharer on knowledge sharers' willingness to share. Design/methodology/approach – The authors conducted two studies, a scenario experimental study and a field survey study to test their hypotheses about the effects of recipients' characteristics on knowledge sharers' willingness to share. Findings – The results revealed that recipients' characteristics play different roles in different situations (responsive and proactive knowledge sharing) in triggering the knowledge sharers' motivation to share. In responsive knowledge sharing, a recipient's learning attitude and personal relationship with the knowledge sharer affected the sharer's willingness to share. In proactive knowledge sharing, a recipient's professional ability and personal relationship with the sharer significantly affected the sharer's willingness to share. Research limitations/implications – The scenario experiment may suffer from the problem of social desirability and the external validity; this study only focuses on the simple main effect of knowledge recipients' characteristics. Practical implications – First, managers should encourage employees to seek information and knowledge from other colleagues, and organizations could provide support for their interaction. Second, managers need to consider the composition of team members. Third, team managers may encourage each member to develop their own special skill or knowledge. Fourth, managers could make some efforts to develop a climate of trust among employees. Social implications – Some organization can also use practice like recognition of internal copyright or patent to protect employees' new ideas or knowledge. Originality/value – First, this study clarifies the relationship between knowledge sharing and other working behaviors. Second, this study contributes to the understanding of how episodic factors affect working behaviors, which has been given little attention in previous research.